FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI TANAMAN PADI GOGO DI KABUPATEN MOROWALI - Abas Abas; Hasmari Noer; If'all If'all (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2019)
This study aims to determine and analyze the factors that affect the yield of gogo rice plants in Morowali District, Central Sulawesi Province. This research was conducted in Morowali District, Central Sulawesi Province. The method used in sampling in this study is simple randomly selected. In this simple random technique each member of the population has the same opportunity to become a sample. This study analyzes the function of results using multiple linear regression analysis. Variable identification is done by listing production factors that are thought to have an effect on the process of upland rice yields. On the factors of production the variables that are affected (dependent variable) are results. While the variables that are variable (independent) affect are the area of ​​land, seeds, fertilizers, pesticides and labor. The results showed that the factors of production of land area, seeds, labor, fertilizers, and pesticides jointly influence the yield of upland rice. Variable land area partially has a significant effect on upland rice yields, with the highest average yield obtained in land area of ​​≤ 0.50 ha (average 3.76 t / ha). Partial variables of seed, labor, fertilizer, and pesticide did not significantly influence the upland rice yield respectively.